Pemberdayaan UMKM Berbasis Digital untuk Meningkatkan Daya Saing Desa Bange, Kabupaten Bengkayang - Ramadhani, Ryca Mazaya; Kalis, Maria Christiana Iman; Semet, Jeane Olivia; Kurniawan, Okki; Richa, Angela (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSME) play a crucial role in supporting regional economic growth, especially in rural areas. However, many MSMEs in Indonesia face various challenges, including limited access to wider markets, low digital literacy, and a lack of knowledge about market trends. In this KKM-PKM activity, a digital-based MSME empowerment program was implemented in Bange Village, Bengkayang Regency, West Kalimantan, by Tanjungpura University, utilizing marketplace platforms and social media. The goal of this activity is to help local MSME expand their market reach and increase competitiveness. Additionally, this activity explores the impact of strengthening literacy in the community through the establishment of a reading corner at SDN 08 Kandasan, as well as the implementation of a posyandu (integrated health service post) program as part of efforts to improve the health of the village community. The results of this activity indicate that digitalization and community-based empowerment not only have the potential to improve the economic conditions of MSME but also bring positive impacts on the overall social welfare and health of the community.